STUDENTS’ EXPERIENCE IN DEVELOPING SPEAKING SKILLS IN ACADEMIC PRESENTATION COURSE - Diva Sabrina Aziezah; Endang Susilawati; Yanti Sri Rezeki; Sumarni; Dewi Novita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study investigates how the Academic Presentation Course supports EFL students in developing their speaking skills through both linguistic and non-verbal aspects. Using a narrative inquiry approach with three participants, the research explored their experiences before, during, and after the course. The findings show that students initially struggled with anxiety, fast speech, and reliance on memorized scripts. However, through guided preparation, rehearsal, and feedback, they improved in fluency, grammar, vocabulary, pronunciation, and comprehension, while also enhancing eye contact, gesture, and intonation. Ultimately, the course fostered both technical competence and confidence, shaping them into adaptable, audience-oriented communicators.